Adaptive capacity to manage permafrost degradation in Northwest Greenland - Jungsberg, Leneisja; Herslund, Lise Byskov; Nilsson, Kjell; Wang, Shinan; Tomaškovičová, Soňa; Madsen, Karl; Scheer, Johanna; Ingeman-Nielsen, Thomas (Polar Geography, 2022)
Global warming has reduced the extent of permafrost, increased permafrost temperatures, and deepened the active layer across the Arctic. Permafrost degradation has detrimental effects on infrastructure and negative impacts on ecosystem services for many Arctic communities. This study examines the adaptive capacity for managing permafrost degradation in Northwest Greenland. The methods are based on questionnaire and interview data from fieldwork, frozen ground temperature records and published data forecasting the deepening of the active layer. Results illustrate the impact of permafrost degradation on the physical environment, hunting and harvesting, housing, and the economy in Northwest Greenland. House owners are mending damage caused by ground movement, and local institutions are concerned with the maintenance of roads and other public infrastructure impacted by permafrost. The scientific knowledge needed to inform decision-making is useful for identifying overall changes, but existing data sources are scarce, and more detailed permafrost maps are needed for long-term town planning. The study concludes that many individuals and institutions engage in autonomous adaptation on an ad hoc basis, rather than pursuing an overall strategy to increase the adaptive capacity in advance of future permafrost degradation in Northwest Greenland.